2015
DOI: 10.1007/s10646-015-1438-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antitoxic defense systems of the freshwater amphipod Gammarus pulex exposed to BDE-47 and BDE-99

Abstract: Polybrominated diphenyl ethers (PBDEs) are emerging pollutants widely distributed in aquatic environment. Although the bioaccumulation of this compound has been well studied, few studies have investigated their impacts on antitoxic systems of invertebrates, considering both genders. Here, we have evaluated the effects of BDE-47 and BDE-99 congeners on the antitoxic defence systems of the freshwater amphipod Gammarus pulex, and especially on the multixenobiotic resistance (MXR) activity, as well as the activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Molecular markers indicate the biological effects of pollutant stresses, which can be used as biomarkers of exposure, especially at low concentrations. Antioxidant enzymes are sensitive biomarkers of aquatic pollution, and have been widely studied in aquatic organisms (Xie et al, 2014;Horion et al, 2015;Shenai-Tirodkar et al, 2017). In the present research, SOD, CAT, and GPx showed quick and sensitive response to BDE-209 stress with time-or dose-dependent manner.…”
Section: Effects Of Bde-209 On the Antioxidant Systemsupporting
confidence: 50%
See 1 more Smart Citation
“…Molecular markers indicate the biological effects of pollutant stresses, which can be used as biomarkers of exposure, especially at low concentrations. Antioxidant enzymes are sensitive biomarkers of aquatic pollution, and have been widely studied in aquatic organisms (Xie et al, 2014;Horion et al, 2015;Shenai-Tirodkar et al, 2017). In the present research, SOD, CAT, and GPx showed quick and sensitive response to BDE-209 stress with time-or dose-dependent manner.…”
Section: Effects Of Bde-209 On the Antioxidant Systemsupporting
confidence: 50%
“…The antioxidant system can scavenge ROS and protect the body from oxidative damage using enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). These enzymes in aquatic animals are sensitively responsive to PBDEs and considered as biomarkers of water pollution (Xie et al, 2014;Horion et al, 2015;Shenai-Tirodkar et al, 2017). However, to our best knowledge, few studies have focused on the effect of BDE-209 on antioxidant enzymes in marine bivalves.…”
Section: Introductionmentioning
confidence: 99%
“…multi-xenobiotics resistance mechanism) pump system, protecting aquatic species against pollutant molecules (Kurelec, 1992), as already investigated in other aquatic invertebrates (i.e. bivalves and crustaceans) (Pain and Parant, 2007;Horion et al, 2015). This MXR system could explain the fact that CLD concentration decreased in the organism and increased in the water over time during the depuration phase, until the renewal at day 3.…”
Section: Cld Behaviour Under In-vitro Conditionsmentioning
confidence: 83%
“…Besides pesticides, chemicals belonging to various classes of environment, food or drinking water contaminants also interfere with human transporters (Nicklisch and Hamdoun, 2020). This is notably the case for chemical additives present in plastics Kim et al, 2007), known to also interact with xenobiotic transporters of aquatic organisms (Anselmo et al, 2012;Horion et al, 2015;Keiter et al, 2016;Nicklisch et al, 2021;Popovic et al, 2014).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%